Gambaran Pondok Pesantrean berbasis Poskestren di Kabupaten Semarang - Dewi Wulandari; Ayu Virahani (Pro Health Jurnal Ilmiah Kesehatan, 2020)
Increasing the scope of public health services is carried out by utilizing the potential and available resources, including those in the community. In accordance with one of the Puskesmas functions, namely the community empowerment center, the puskesmas is tasked with empowering the community in the health sector, namely through the Community-Based Health Efforts (UKBM) with one of the real forms being the Pesantrean Health Post (Poskestren). This study aims to obtain an overview of the implementation of the poskestren in boarding schools in the area of Semarang District Health Office. This research is a descriptive observational study with a secondary data study obtained from health promotion and community empowerment data reports collected from 2017 to 2019 by the Semarang District Health Office. The population in this study were all boarding schools reported in the working area of Semarang Regency in 2017-2019. The sample in this study is a boarding school that already has a poskestren in the working area of Semarang Regency in 2017-2019. The research data was then analyzed descriptively. The results obtained are an increase in the number and activities of implementing the poskestren from 2017-2019.